Lighting the way: an economical alternative to feeder cell irradiation for T-cell expansion - Benavidez Arias, Michael; Nguyen, An; Ross, Daniel; Eagerton, David; Ritthipichai, Krit (Frontiers in Immunology, 2024)
A robust T-cell expansion process involves co-culturing T-cells with non-proliferating feeder cells combined with anti-CD3 antibody and IL-2. Although ionizing irradiation effectively inhibits feeder cell proliferation, the high operating costs limit cell therapy research to well-funded institutions. UVC, known for causing DNA damage-induced cell death and commonly used for environmental sterilization, presents a cost-effective alternative to ionizing irradiation for generating non-proliferating feeder cells. UVC irradiation of K562 artificial antigen presenting cells (aAPCs) resulted in significant DNA damage, evidenced by increased γ-H2AX phosphorylation within 15 minutes and elevated 8-OHdG levels at 24 hours. This indicates the occurrence of DNA double-strand breaks and oxidative damage. Following UVC irradiation, glucose uptake and ATP production were significantly reduced, whereas aCD3 retention at the surface of the cell increased twofold. Selective inhibition of glucose uptake and ATP production similarly enhanced aCD3 retention by approximately 10-fold and 6-fold, respectively. This suggests that UVC-induced energy deprivation dampens aCD3 internalization, potentially enhancing T-cell activation through prolonged aCD3 and T-cell receptor interaction. Tumor-infiltrating lymphocytes (TILs) expanded with UVC-irradiated PBMCs demonstrated comparable viability, expansion, immunophenotype, and effector function to those expanded with ionizing irradiation. UVC irradiation was equally effective in suppressing feeder cell proliferation and facilitating the expansion of functionally potent T-cells compared to traditional ionizing irradiation. Implementing UVC irradiation in T-cell expansion can significantly reduce costs, enhancing the accessibility and feasibility of cell therapy research across various institutions.